CSR Sebagai Moderasi Hubungan GCG Terhadap Nilai Perusahaan Farmasi Tahun 2018-2020 - Dwi Almira Zuleika; Yefta Andi Koesnugroho (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to analyze and provide empirical evidence on whether CSR moderates the relationship between Good Corporate Governance behavior and the increase in corporate value in pharmaceutical companies listed on the IDX in 2018-2020. Research related to CSR as a moderation in the relationship between GCG and corporate value in pharmaceutical companies is difficult to find so this research was chosen to be conducted, considering that the performance of pharmaceutical companies is increasing due to the covid-19 pandemic.. This research method is included in quantitative descriptive research that uses purposive sampling techniques and found 4 pharmaceutical companies with a sample of 48 obtained from the company's quarter report. Hypothesis testing uses multiple linear regression and moderated regression analysis (MRA). The results of the study found that GCG affects the value of the company while CSR as moderation has no effect on the value of the company. Conclusions in the research are obtained if GCG is done to minimize conflicts between interested parties in the entity, while CSR practices are the obligations of each entity, so that pharmaceutical entities must have disclosed CSR well following the provisions of the legislation without the need to be monitored by investors